Autocracy and Health Governance in Russia - Kravtsov, Vlad. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
The book is the first attempt to investigate how and to what extent authoritarian (personalistic) regimes fail to provide fundamental goods and services. For two decades, Russian authorities spent much effort and money to improve health administration, but most success stories are borderline fake. The failure is by design; because personalistic regimes rely on personalized exchanges and bargains instead of impersonal rules and permanent organizations, all actors put self-interest ahead of patients' needs. It is a severe problem because authoritarian principals proclaim social betterment as their central goal -- and many Russians take such claims at face value -- but incentivize their agents to imitate progress and tolerate slipshod performance. The benefits of this investigation are three-fold. First, the book provides an analytical framework of bad governance rooted in the rational institutionalist tradition and connected to competence-control theory. Second, it gives a general readership interested in how Russia works a sense of the key political players' mindset and the regime-induced constraints under which elites operate. Third, although the book investigates health governance exclusively, its analytical framework is portable to other issue areas and could be applied to explain how and why Russia evolved into an ineffective, coercive, and predatory state under Putin's leadership. Vlad Kravtsov is Associate Professor of Political Science & Law at Spring Hill College, the US. .
Chapter 1. Personalistic regimes and the processes of governance -- Chapter 2. Providing goods: health mandates and authoritarian performance -- Chapter 3. Managing actors: faulty controls and flawed performance -- Chapter 4. Constructing the oversight: organizational atrophy and particularized exchanges -- Chapter 5. Securitizing the epidemic: ideological adaptations and illiberal meanings -- Chapter 6. Conclusions, implications, and dashed hopes.
Keywords: Europe-Politics and government; Russia-History.; Europe, Eastern-History.; Soviet Union-History.; European Politics; Russian, Soviet, and East European History